Survival after resection of appendiceal carcinoma by hemicolectomy and less radical than hemicolectomy: a population-based propensity score matched analysis - Elias, Hanna; Galata, Christian; Post, Stefan; Marti, Lukas (Colorectal disease, 2017)
Aim The operative treatment for non-metastatic appendiceal carcinoma is controversial despite the recommendation of right hemicolectomy (RH) by many researchers. The aim of this population-based study was to compare outcomes after RH and less radical resection than right hemicolectomy (LRH). Method A total of 1144 patients who underwent resection with additional lymphadenectomy of Stages I-III appendiceal carcinoma from 2004 to 2012 were identified in the Surveillance, Epidemiology and End Results database. Overall survival (OS) and cancer-specific survival (CSS) after RH and LRH were assessed by unadjusted and risk-adjusted Cox regression analysis and by propensity score matched analysis. Results A total of 855 (74.7%) patients underwent RH and 289 (25.3%) underwent LRH. In an unadjusted analysis, survival after LRH and RH did not differ in OS [hazard ratio (HR) 0.95, 95% CI 0.71-1.26, P = 0.707] and CSS (HR 0.95, 95% CI 0.69-1.32, P = 0.762). The 5-year OS and CSS in patients who underwent RH were 71.6% (95% CI 67.8-75.6%) and 76.4% (95% CI 72.8-80.3) compared with 73.8% (95% CI 67.9-80.2) and 78.7% (95% CI 73.2-84.7) in patients with LRH, respectively. No relevant difference in survival between LRH and RH could be observed in a multivariable analysis (OS, HR 0.90, 95% CI 0.65-1.25, P = 0.493; CSS, HR 0.87, 95% CI 0.60-1.26, P = 0.420) and after propensity score adjusted analysis (OS, HR 0.87, 95% CI 0.62-1.22, P = 0.442; CSS, HR 0.97, 95% CI 0.67-1.40, P = 0.883). Conclusions In this retrospective analysis, survival after RH for non-metastatic appendiceal carcinoma was not statistically significantly superior to LRH. Hence, LRH with lymphadenectomy might be sufficient for treatment of non-metastatic appendiceal carcinoma.
Gesehen am 06.11.2018